29 Caregiver-Reported Delay in Presentation to Pediatric Emergency Departments for Fear of Contracting COVID-19: A multinational cross-sectional study. (29th October 2021) - Davis, Adrienne; Sunderji, Alia; Marneni, Shashidhar; Seiler, Michelle; Hall, Jeanine; Cotanda, Cristina Parra; Klein, Eileen; Brown, Julie; Gelernter, Renana; Griffiths, Mark; Hoeffe, Julia; Gualco, Gianluca; et al.
Abstract: Primary Subject area: Public Health and Preventive Medicine Background: Visits to pediatric emergency departments have decreased up to 75% during the pandemic, with corresponding increases in high acuity visits, inpatient admissions, and intensive care unit admissions compared to historical cohorts. Objectives: To determine if caregivers of children presenting to pediatric emergency departments (EDs) during the COVID-19 pandemic are delaying presenting to care for fear of contracting COVID-19. Secondary objectives were to: a) evaluate potential predictors of delay; b) describe the proportion of children whose symptoms worsened during time to presentation. Design/Methods: A multicentre cross-sectional survey study of caregivers accompanying their children aged 0-19 years old to 16 pediatric EDs in 6 countries, from May-June 2020. An anonymous online survey, completed by caregivers via RedCAP, included caregiver and child demographics, presenting complaints, if they delayed presentation and whether symptoms worsened during this interval, as well as caregiver concerns about the child or caregiver having COVID-19 at the time of ED visit. Results: Of 1543 caregivers completing the survey, 287 (18.6%) reported a delay in seeking ED care due to concerns of contracting COVID-19 in the hospital. Of those, 124 (43.2%) stated their child's symptoms worsened during the waiting interval. Caregiver relationship to child [mother] (OR 1.85, 95% CI 1.27-2.76), presence of chronic illness in child (OR 1.78. 95% CI 1.14-2.79), younger age of caregiver (OR 0.965, 95% CI 0.943-0.986), and caregiver concerns about lost work during the pandemic (OR 1.08, 95% CI 1.04-1.12), were independently associated with a COVID-19-related delayed presentation in multivariate regression analysis. Conclusion: Almost one in five caregivers reported delaying ED presentation for their ill or injured child, specifically due to fear of contracting COVID-19 while in hospital. Mothers, younger caregivers, caregivers of children with chronic illness, and those concerned about lost work were at highest risk for delay.